2020
DOI: 10.1016/j.heliyon.2020.e03493
|View full text |Cite
|
Sign up to set email alerts
|

Efficient differentiation and purification of human induced pluripotent stem cell-derived endothelial progenitor cells and expansion with the use of inhibitors of ROCK, TGF-β, and GSK3β

Abstract: Endothelial cells (ECs) and endothelial progenitor cells (EPCs) play crucial roles in maintaining vascular health and homeostasis. Both cell types have been used in regenerative therapy as well as in various in vitro models; however, the properties of primary human ECs and EPCs are dissimilar owing to differences in genetic backgrounds and sampling techniques. Human induced pluripotent stem cells (hiPSCs) are an alternative cell source of ECs and EPCs. However, owing to the low purity of differentiated cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 49 publications
(51 reference statements)
4
19
0
Order By: Relevance
“…ARHGDIA overexpression did not seem to adversely affect self-renewal or differentiation, as ARHGDIA-transduced cultures were maintained for several months and differentiated into EBs comprising all three germ layers. This is consistent with the routine use of ROCKi for hPSC culture; however, some laboratories have begun to report using ROCKi in differentiation protocols [38][39][40][41].…”
Section: Discussionsupporting
confidence: 70%
“…ARHGDIA overexpression did not seem to adversely affect self-renewal or differentiation, as ARHGDIA-transduced cultures were maintained for several months and differentiated into EBs comprising all three germ layers. This is consistent with the routine use of ROCKi for hPSC culture; however, some laboratories have begun to report using ROCKi in differentiation protocols [38][39][40][41].…”
Section: Discussionsupporting
confidence: 70%
“…In 2013, Bai et al, found that during the derivation of vascular endothelial cells from human ESCs, the expression level of TGF-β increased from the fourth day of differentiation, and the addition of TGF-β type I receptor inhibitor SB431542 reduced the expression levels of mesodermal markers and the number of endothelial progenitors upon mesoderm induction [37]. In 2020, when Aoki et al, derived endothelial cells from human iPSCs, they found that the combination of three small molecules, namely, Y-27632 (a selective inhibitor of ROCK), A83-01 (a receptor-like kinase inhibitor of TGF-β) and CHIR-99021 (a selective inhibitor of GSK3β), improved the expansion of endothelial cells [36]. In our study, during the induction of porcine iPSCs into vascular endothelial cells, the addition of SB431542 at the early stage of differentiation inhibited the expression of mesoderm-specific genes, while the addition of SB431542 at the later stage of differentiation increased the expression of endothelial-specific genes, suggesting that TGF-β signaling plays a positive role in mesoderm formation and a negative role in its further endothelialization.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above results from bioinformatic analysis and the roles of TGF-β signaling in the development of human and mouse endothelial cells [34][35][36][37], we firstly…”
Section: Effects Of Tgf-β On the Differentiation Of Porcine Ipsc-ecsmentioning
confidence: 99%
See 1 more Smart Citation
“…A83-01, an effective inhibitor of TGF-β type I receptor (ALK5-TD), promotes cell proliferation 52 and colonosphere formation 53 . Y-27632, A83-01, and CHIR99021 are often used together to improve cell survival and cell proliferation 51 , 54 .…”
Section: Construction Of Pdosmentioning
confidence: 99%